2017
DOI: 10.1038/s41598-017-05857-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined deletion and DNA methylation result in silencing of FAM107A gene in laryngeal tumors

Abstract: Larynx squamous cell carcinoma (LSCC) is characterized by complex genotypes, with numerous abnormalities in various genes. Despite the progress in diagnosis and treatment of this disease, 5-year survival rates remain unsatisfactory. Therefore, the extended studies are conducted, with the aim to find genes, potentially implicated in this cancer. In this study, we focus on the FAM107A (3p14.3) gene, since we found its significantly reduced expression in LSCC by microarray profiling (Affymetrix U133 Plus 2.0 arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…67 candidate marker genes were identified that strongly correlated with the human BP/bRG population (Pollen et al, 2014, 2015). Genes were highlighted related to extracellular matrix formation, migration and stemness, including TNC (Garcion et al, 2004), PTPRZ1 (Baldauf et al, 2015), FAM107A (Kiwerska et al, 2017), HOPX (Yap et al, 2016), and LIFR (Wu et al, 2018). Importantly, LIFR/STAT3 signaling was found to be required for bRG cell cycle progression and selectively expressed by bRGs (Pollen et al, 2015).…”
Section: Characteristics Of Brgsmentioning
confidence: 99%
“…67 candidate marker genes were identified that strongly correlated with the human BP/bRG population (Pollen et al, 2014, 2015). Genes were highlighted related to extracellular matrix formation, migration and stemness, including TNC (Garcion et al, 2004), PTPRZ1 (Baldauf et al, 2015), FAM107A (Kiwerska et al, 2017), HOPX (Yap et al, 2016), and LIFR (Wu et al, 2018). Importantly, LIFR/STAT3 signaling was found to be required for bRG cell cycle progression and selectively expressed by bRGs (Pollen et al, 2015).…”
Section: Characteristics Of Brgsmentioning
confidence: 99%
“…It is also known as Tohoku University cDNA clone A on chromosome 3 (TU3A) or Family with sequence similarity 107, member A (FAM107A) [24,25]. DRR1 is downregulated in various cancer cell lines, including renal cell, ovarian, cervical, laryngeal, gastric, prostate, liver, lymph, and non-small cell lung cancer and is associated with the progression of neuroblastoma, meningioma and malignant glioma [26,27,28,29,30,31,32,33,34,35,36]. On the other hand, DRR1 is highly expressed in outer radial glial cells [37] and in the invasive component of glioblastoma [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…LSCC cell lines ( n = 16) established at the Turku University Central Hospital (Finland) and previously cytogenetically characterized, were used in this study (Supplementary Table S1A). Cell culture conditions and further characteristics can be found elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The cell lines were incubated with 0.1 µM and 0.3 µM DAC concentrations in the culture medium and, as the control the same cell lines were incubated with the same volume of 50% acetic acid (aa) (solvent used to prepare DAC dilutions). Detailed description of the procedure was published recently . The demethylation experiments with decitabine were performed in duplicates for UT‐SCC‐11 and triplicates for UT‐SCC‐29 cell lines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation